Value of SOFA Scores in Predicting Prognosis in Patients with Ventilator Associated Pneumonia - Harprit Kaur Madan (International Journal of Anatomy Radiology and Surgery, 2016)
Introduction: Ventilator-associated pneumonia (VAP) is a frequent infection in patients on mechanical ventilators in intensive care units (ICU) .The prediction of its outcome is important in the decision-making process and management. Critical care scoring system derives a value which helps in the prediction and prognosis of the patient in ICU. Aim: The objective of this study was to assess the value of Sequential Organ Failure Assessment (SOFA) score in prediction of mortality in patients with VAP, to outline the incidence, type of infection, morbidity outcome and mortality and to correlate SOFA score with mortality in VAP in mechanically ventilated patients. Study Design: Prospective observational study. Materials and Methods: Fifty patients who were admitted to the ICU and who were on mechanical ventilation for more than 48 hours and developed ventilator associated pneumonia were included in the study. Patients were followed till discharge/death. Clinical and laboratory data conforming to the SOFA scores were recorded on day of admission and SOFA and CPIS scores recorded on the day of the diagnosis of VAP and correlated with mortality and duration of stay in ICU. Statistical Analysis: Following test were used to analyze the data: Mann-Whitney test, Pearson Chi-Square and Fisher’s Exact Test. The continuous variable SOFA score was categorized into classes by selecting the best cut-offs (Receiver-operating characteristic analysis, ROC). Results: Mortality rate was 54%. Eight patients had bacteraemia at the same time with the same organisms as those causing VAP. The mean SOFA in survivors (3.57) and non survivors (5.19) and the sofa score in survivors (8.09) and non survivors (11.67) scores determined at the time of VAP diagnosis were significantly higher in non survivors than in survivors. Area under receiver operating characteristic (ROC) curve for SOFA score on day of diagnosis of VAP was 0.816 with SOFA > 11 (sensitivity: 78, specificity: 83), p = 0.005). Conclusion: Thus, we concluded that SOFA score is a very useful score to predict the mortality and morbidity of patients admitted in ICU. It is a simple, but effective prognostic indicator and evaluator for patient progress in ICU.